Effects of gold nanoparticles size and Concentration on image contrast in ct Imaging - Othaman, Siti Nor Shikha (Universiti Sains Malaysia, 2016)
To compare the variation of CT contrast enhancement effect from the different gold nanoparticles (AuNps) size and concentration. Contrast enhancements by AuNps were evaluated in term of different AuNPs sizes and concentration as well as various CT scan kernel reconstruction and tube voltages setting. Different sizes of AuNps were investigated which are 1.9nm, 15nm, 20nm, and 40nm in 1mMol volume. AuNPs concentration tested are between 3mMol to 40mMol for 1.9nm and 15nm size of samples. The respective samples of AuNps were scanned under CT SOMATOM Definition AS scanner at various tube voltages from 80 kVp to 140kVp at 410 mAs and different type of kernel reconstruction modes. The regions of interests (ROI) were drawn on the image to obtain the CT value (Hounsfield Unit). AuNPs of 15 nm has shown the highest CNR for both head and abdomen protocol which was 113% and 75.96% different compared to 1.9 nm at 120 kVp. Meanwhile, for the different concentration of AuNPs, 1.9 nm contributed the highest CNR at 15 mMol for both head and abdomen protocol while the 15 nm provided highest CNR at 20 mMol concentration. The standard deviation (SD) of different kernel for different AuNPs sizes and concentration indicate lower SD for the head protocol compared to abdomen protocol. AuNPs size and concentration has significant influence on CT contrast enhancement. The choice of tube voltage could alter the enhancement effect as the CNR value dependent on the attenuation level proportion to the kVp. The kernel reconstruction mode also plays important role to the contrast enhancement.